Enhanced detection of viral diversity using partial and near full‐length genomes of human immunodeficiency virus Type 1 provirus deep sequencing data from recently infected donors at four blood centers in Brazil. Issue 5 (21st November 2014) - Pessôa, Rodrigo; Watanabe, Jaqueline Tomoko; Calabria, Paula; Alencar, Cecilia Salete; Loureiro, Paula; Lopes, Maria Esther; Proetti, Anna Barbara; Félix, Alvina Clara; Sabino, Ester C.; Busch, Michael P.; Sanabani, Sabri S.; International Component of the NHLBI Recipient Epidemiology and Donor Evaluation Study‐III (REDS‐III)
<x xml:space="preserve">Abstract</x> Background Here, we report application of high‐throughput near full‐length genome (NFLG) and partial human immunodeficiency virus Type 1 (HIV‐1) proviral genome deep sequencing to characterize HIV in recently infected blood donors at four major blood centers in Brazil. Study Design and Methods From 2007 to 2011, a total of 341 HIV+ blood donors from four blood centers were recruited to participate in a case‐control study to identify HIV risk factors and motivations to donate. Forty‐seven (17 from São Paulo, eight from Minas Gerais, 11 from Pernambuco, and 11 from Rio de Janeiro) were classified as recently infected based on testing by less‐sensitive enzyme immunoassays. Five overlapping amplicons spanning the HIV genome were polymerase chain reaction amplified from peripheral blood mononuclear cells. The amplicons were molecularly barcoded, pooled, and sequenced by a paired‐end protocol (Illumina). Results Of the 47 recently infected donor samples studied, 39 (82.9%) NFLGs and six (12.7%) partial fragments were de novo assembled into contiguous sequences and successfully subtyped. Subtype B was the only nonrecombinant virus identified in this study and accounted for 62.2% (28/45) of samples. The remaining 37.8% (17/45) of samples showed various patterns of subtype discordance in different regions of HIV‐1 genomes, indicating two to four circulating recombinant subtypes derived from Clades B, F, and C. Fourteen samples (31.1%) from this study harbored drug resistance mutations, indicating higher rate of drug resistance among Brazilian blood donors. Conclusion Our findings revealed a high proportion of HIV‐1 recombinants among recently infected blood donors in Brazil, which has implications for future blood screening, diagnosis, therapy, and vaccine development.